Gender Issues in Two Recent Hispanic American Films: 108. Cuchillo de Palo by Renate Costa and Pelo Malo by Mariana Rondón (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
This article proposes an analysis of two recent Hispanic American films: 108. Cuchillo de palo (2010) by Paraguayan director Renate Costa and Pelo malo (2013) by Venezuelan director Mariana Rondón. Starting from the documentary in which family history and collective history converge, a brief review of the anti-homosexual repression of the government of Alfredo Stroessner is presented, before showing how the two works deal with the subject of the identity search of the two protagonists, Rodolfo Costa, the uncle of Renate Costa, and Junior, a nine-year-old boy who dreams of having smooth hair in Mariana Rondón’s film. If some consider the attitude of both characters as «abnormal» because they transgress the heteropatriarchal norms in force in Paraguay and Venezuela, our article states that the two main detractors, Rodolfo Costa’s brother and Junior’s mother, do not completely obey the normative codes of their respective society either. The final section shows that the two films, although they focus on the subject of tolerance, formulate different endings: in contrast to 108. Cuchillo de palo, hope seems absent in Pelo malo.Key words: Hispanic American cinema, homosexuality, gender, transgression, tolerance.